Inhibitors of Sterol Biosynthesis and Amphotericin B Reduce the Viability of Pneumocystis carinii f. sp. carinii - Kaneshiro, Edna S. (American Society for Microbiology (ASM), 2000)
Pneumocystis carinii synthesizes sterols with a double bond at C-7 of the sterol nucleus and an alkyl group with one or two carbons at C-24 of the side chain. Also, some human-derived Pneumocystis carinii f. sp. hominis strains contain lanosterol derivatives with an alkyl group at C-24. These unique sterols have not been found in other pathogens of mammalian lungs. Thus, P. carinii may have important differences in its susceptibility to drugs known to block reactions in ergosterol biosynthesis in other fungi. In the present study, inhibitors of 3-hydroxy-3-methyglutaryl coenzyme A reductase, squalene synthase, squalene epoxidase, squalene epoxide-lanosterol cyclase, lanosterol demethylase, Δ(8) to Δ(7) isomerase, and S-adenosylmethionine:sterol methyltransferase were tested for their effects on P. carinii viability as determined by quantitation of cellular ATP levels in a population of organisms. Compounds within each category varied in inhibitory effect; the most effective included drugs targeted at squalene synthase, squalene epoxide-lanosterol cyclase, and Δ(8) to Δ(7) isomerase. Some drugs that are potent against ergosterol-synthesizing fungi had little effect against P. carinii, suggesting that substrates and/or enzymes in P. carinii sterol biosynthetic reactions are distinct. Amphotericin B is ineffective in clearing P. carinii infections at clinical doses; however, this drug apparently binds to sterols and causes permeability changes in P. carinii membranes, since it reduced cellular ATP levels in a dose-dependent fashion.